2022
DOI: 10.3390/molecules27144473
|View full text |Cite
|
Sign up to set email alerts
|

Putative Biosynthesis of Talarodioxadione & Talarooxime from Talaromyces stipitatus

Abstract: Polyesters containing 2,4-dihydroxy-6-(2-hydroxypropyl)benzoate and 3-hydroxybutyrate moieties have been isolated from many fungal species. Talaromyces stipitatus was previously reported to produce a similar polyester, talapolyester G. The complete genome sequence and the development of bioinformatics tools have enabled the discovery of the biosynthetic potential of this microorganism. Here, a putative biosynthetic gene cluster (BGC) of the polyesters encoding a highly reducing polyketide synthase (HR-PKS) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The production of beneficial biotechnological metabolites by the T. pinophilus isolate in this study can be linked to the putative biosynthetic gene cluster previously reported in some fungal isolates, including the genera Talaromyces [ 6 , 49 ]. A comparative genomic analysis of T. pinophilus 1–95 revealed that the fungal strain contained 68 metabolism gene clusters containing 401 putative genes, including Type1 polyketide synthase genes and nonribosomal peptide synthase genes [ 6 ].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The production of beneficial biotechnological metabolites by the T. pinophilus isolate in this study can be linked to the putative biosynthetic gene cluster previously reported in some fungal isolates, including the genera Talaromyces [ 6 , 49 ]. A comparative genomic analysis of T. pinophilus 1–95 revealed that the fungal strain contained 68 metabolism gene clusters containing 401 putative genes, including Type1 polyketide synthase genes and nonribosomal peptide synthase genes [ 6 ].…”
Section: Discussionsupporting
confidence: 65%
“…The authors found that T. pinophilus 1–95 contains more secondary metabolites than other related filamentous fungi, promoting the cultivation of T. pinophilus for the high synthesis of beneficial metabolites. In addition, Ahmed [ 49 ] complete genome sequence of T. stipitatus and the advancement in bioinformatics tools have facilitated the discovery of the fungus’s biosynthetic potential, with the identification of a putative biosynthetic gene cluster (BGC) of the polyesters encoding a highly reducing polyketide synthase (HR-PKS) and nonreducing polyketide synthase (NR-PKS). According to Le Govic et al [ 50 ], these genes are responsible for forming several metabolites in bacterial and fungal species.…”
Section: Discussionmentioning
confidence: 99%
“…Additional domain dissection experiments, including the use of 1 loaded to purified ACP Preu6 , are under way in our labs to gain a full mechanistic understanding of this intricate dimerization process and the exact nature of the SAT‐TE collaboration. In the meantime, investigations of direct SAT‐TE interactions in other fungal nrPKS systems forming oligomeric products such as the polylactone synthases may also be considered [20, 21] …”
Section: Figurementioning
confidence: 99%
“…In the meantime, investigations of direct SAT-TE interactions in other fungal nrPKS systems forming oligomeric products such as the polylactone synthases may also be considered. [20,21]…”
Section: Angewandte Chemiementioning
confidence: 99%